Understanding student engagement in vaccination education: an interview-based multi-stakeholder study - Schlopsna, Melissa; Scheersoi, Annette (Frontiers in Public Health, 2024)
The COVID-19 pandemic has underscored the importance of informed decision-making, especially concerning vaccination for disease prevention. This highlights the need for scientific literacy, trust, and understanding of relevant concepts such as pathogens, immune responses, and transmission pathways. Additionally, societal and ethical considerations are integral for a comprehensive approach. While collaborating with medical professionals and fostering argumentation and decision-making skills hold promise for enhancing engagement with these topics in educational settings, understanding students’ perspectives is essential for maintaining their motivation to learn and their interest in such complex subjects. Therefore, a qualitative study involving interviews with secondary school students, experienced educators, and vaccination experts familiar with school environments was conducted to identify factors fostering student engagement and interest in immunobiology and vaccines. The findings highlight focal areas of student interest in the topic and the value of involving students in lesson planning. They also underscore the importance of real-world relevance and the need for clear, student-centered communication with medical professionals. Recommendations for educators include integrating interactive learning activities, real-world examples, and case studies.